EXPLORING THE LEVEL AND PRIMARY CAUSES OF PUBLIC SPEAKING ANXIETY AMONG ENGLISH DEPARTMENT STUDENTS - Kenti Sugiyati; Lilia Indriani (Universitas Teknokrat Indonesia, 2021)
English public speaking anxiety is a crucial issue experienced by students and it needs to be coped with acknowledging the importance of public speaking proficiency concerning today's demands. As EFL students, many studies have found that they encountered a considerable level of public speaking anxiety in which significantly affects their speaking quality. Therefore, measuring students' public speaking anxiety is essential since it can help both the students and teachers to know the level and primary causes of public speaking anxiety so that effective strategies can be designed to overcome this particular issue. Hence, the researchers attempt to investigate the level and primary causes of EFL students' public speaking anxiety. This present study participated by 34 third-semester students of the English Department at Universitas Tidar. In collecting the data regarding the public speaking anxiety level, the researchers used the Public Speaking Class Anxiety Scale (PSCAS) proposed by Yaikhong & Usaha (2012). Furthermore, the results from the questionnaire are delineated to explore the causes of public speaking anxiety. The study found that 58.8% of students experienced a medium level of public speaking anxiety. In addition, most of the students agreed that fear of negative evaluation becomes the major anxiety-provoking factor following by communication apprehension and test anxiety—lastly, only almost half of the students’ experience comfort in speaking English.